Maxillary Sinus Pneumocele - N. A. Savrasova; Yu. M. Melnichenko; S. L. Kabak; A. B. Perminov (Вестник рентгенологии и радиологии)
Hyperpneumatization of the paranasal sinuses is a rare condition. Hypersinus, pneumosinus dilatans, and pneumocele are the three types of excessive pneumatization according to the traditional classification proposed by Urken et al. (1987). If in the first case, no treatment is required, but the latter two may be accompanied by aesthetic and/or functional disorders or may result in pressure effects on adjacent anatomical objects, therefore they require surgical correction. Maxillary sinus pneumocele is described in few publications. The presented case demonstrates typical clinical and radiographic signs of the maxillary sinus pneumocele, as well as hypersinus on the contralateral side. Cone beam computed tomography scans in combination with anamnestic and clinical data provide key information for the diagnosis of maxillary sinus pneumocele, as well as for differential diagnosis with other variants of their excessive pneumatization.